Psychological features of development of the student’s personality in conditions of high school - S. V. Khrebina; M. V. Khrebin (Вестник Северо-Кавказского федерального университета, 2022)
The study implied investigation into the features of personality development in students; there is also a presentation of the results from developing and implementing the programme aimed at successful student personality development through their training in university. There is a view on the psychological conditions facilitating efficient personality development through professional training